IMPROVING STUDENTS’ MOTIVATION OF MECHANICAL ENGINEERING STTR CEPU IN WRITING RESEARCH PAPERS USING TRAINING STRATEGY - Helmi Gunawan (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2019)
The purpose of this study is (1) to illustrate whether training strategy in the research can increase students writing motivation and (2) to find out the advantages and disadvantages of training strategy in the research for students of Mechanical Engineering STTR Cepu. This School Action Research was carried out in 2 cycles. Each cycle 1 includes 2 meetings, while cycle 2 is 1 meeting. The data used in this study is qualitative data. Qualitative data is taken from observations, questions and answers, questionnaires, and product results. The data has been analyzed using the Constant Comparative Method. The findings of the study using a training strategy are: (1) increasing students writing motivation, including: a) curiosity, b) students’ effort, c) students’ perseverance, and d) students’ experience. The increase can also be shown by the average number of participants from each meeting increasing and the product results of students also increasing. There are 12 research titles and there are 2 research proposals made by participants. Based on the results of the study, it can be concluded that the training in the preparation of research can increase students’ motivation to write.